Garuda’s Valor: Eksplorasi Sejarah Perang Bojong Kokosan Melalui Game 3d Third Person Shooter Dengan Algortima A* - Chelika Patricia Handraputri; Kamdan Kamdan; Bibin Aripin; Muhammad Azmi Fauzan; Alun Sujjada (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2024)
This research applies the A* algorithm in the 3D Third Person Shooter (TPS) game "Garuda's Valor" with a historical theme. The focus is on optimizing character navigation and movement responsiveness for an immersive gameplay experience. The method includes designing the A* algorithm, testing responsiveness, and assessing its impact on game appeal and user satisfaction. The study also integrates historical elements of the Bojong Kokosan battle to provide valuable educational experiences. Challenges include complex terrain and dynamic obstacles, aiming to create a realistic and engaging environment. This project explores the balance between historical accuracy and engaging gameplay, and analyzes the algorithm's efficiency. "Garuda's Valor" sets a new standard in educational games, combining fun and learning through advanced artificial intelligence.